2020
DOI: 10.1186/s12944-019-1122-4
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Pyk2 pathway and reactive oxygen species (ROS) to the anti-cancer effects of eicosapentaenoic acid (EPA) in PC3 prostate cancer cells

Abstract: Background n-3 polyunsaturated fatty acids (n-3 PUFAs), including eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), are thought to exert protective effects in cardiovascular diseases. In addition, n-3 PUFAs have demonstrated anti-cancer effects in vitro and in vivo. Objective We investigated the anti-cancer effects and mechanism of action of EPA on PC3 prostate cancer cells in vitro. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 55 publications
4
6
1
Order By: Relevance
“…It inhibits the phosphorylation of proline-rich tyrosine kinases (PYK2) and ERK and induces overproduction of ROS, exerting antiproliferative effects in PC-3. This anticancer effect has been pointed out by Oono et al as dose-dependent, decreasing PC-3 cell proliferation, migration, and invasion . Consistent with a potential increase of the ROS species, we observed a significant decrease in the antioxidant molecule glutathione (log 2 FC = −3.02, p -value < 0.05) in PC-3 ZIKV-infected cells, while this marker was not even detected in PNT1a.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It inhibits the phosphorylation of proline-rich tyrosine kinases (PYK2) and ERK and induces overproduction of ROS, exerting antiproliferative effects in PC-3. This anticancer effect has been pointed out by Oono et al as dose-dependent, decreasing PC-3 cell proliferation, migration, and invasion . Consistent with a potential increase of the ROS species, we observed a significant decrease in the antioxidant molecule glutathione (log 2 FC = −3.02, p -value < 0.05) in PC-3 ZIKV-infected cells, while this marker was not even detected in PNT1a.…”
Section: Discussionsupporting
confidence: 90%
“…This anticancer effect has been pointed out by Oono et al as dose-dependent, decreasing PC-3 cell proliferation, migration, and invasion. 38 Consistent with a potential increase of the ROS species, we observed a significant decrease in the antioxidant molecule glutathione (log 2 FC = −3.02, p-value < 0.05) in PC-3 ZIKVinfected cells, while this marker was not even detected in PNT1a. The reduction of antioxidants may lead to apoptosis signaling.…”
Section: Zikv Effects On Prostate Cells Is Cell-type Dependentsupporting
confidence: 77%
“…in the present study, the protective mechanism of dHa in the inhibition of VSMc proliferation and migration was investigated. Previous studies on the protective effect of dHa in cardiovascular diseases focused on changes in gene expression (29,30). The present study demonstrated that the inhibitory effect of dHa on the proliferation and migration of VSMcs is mediated by microrna-155 downregulation.…”
Section: Discussionsupporting
confidence: 61%
“…Additionally, in a first attempt to understand the cytotoxicity mechanism of the microalgal extracts in the tumorigenic cells, the effect of omega-3 lipid extracts on cellular ROS levels of HCT-116 cells was investigated with the DCF assay (Figure 6). Different studies have shown that the accumulation of certain PUFAs leads to increased lipid peroxidation and the generation of intracellular radical species that may be toxic to cancer cells [42,47,49,50]. However, in this study and under the conditions tested, the incubation of HCT-116 cells with the microalgal lipid extract did not result in a significant increase in intracellular ROS levels regardless of the concentration or type of extract used (p > 0.05).…”
Section: Cytotoxic Activity Of Lipid Extracts From Nannochloropsis Ga...contrasting
confidence: 70%